2016
DOI: 10.31686/ijier.vol4.iss5.537
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting the Implementation Guidance and Counselling Services in Secondary Schools in the Ohangwena Region of Namibia

Abstract: The study aimed to establish teacher counsellors’ views on the factors impacting the implementation of guidance and counselling services in the Ohangwena region of Namibia. The study was quantitative in nature and used a non experimental design that involved a survey. The population of the study comprised of teacher counsellors in all senior secondary schools in Ohangwena region. Data were collected using questionnaires which were administered to a sample of twenty six (26) teacher counsellors. Teacher counsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 1 publication
4
7
0
Order By: Relevance
“…The present study also revealed that other ways in which guidance can be improved are proper training and retraining of counsellors, the promulgation of policies and sensitisation. These findings are consistent with those of Mbongo (2013), Odeleye (2017) and Waititu and Khamasi (2010). Effective guidance and counselling service delivery depends largely on the counsellor's training (Tsikati, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study also revealed that other ways in which guidance can be improved are proper training and retraining of counsellors, the promulgation of policies and sensitisation. These findings are consistent with those of Mbongo (2013), Odeleye (2017) and Waititu and Khamasi (2010). Effective guidance and counselling service delivery depends largely on the counsellor's training (Tsikati, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Both the quantitative (73.0%, see Table 2) and qualitative data converge that policies are required. Introducing peer counsellors, reducing the workload for counsellors or allocating more time for counselling, and motivating counsellors are some of the ways in which guidance and counselling can be improved (Mbongo, 2013;Waititu & Khamasi, 2010). Undoubtedly, these are all issues that can be driven by policy.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kamore and Tiego (2013) observed that inadequate support by school managers and resource input were some of the challenges impacting negatively on guidance and counselling in schools. This finding concurs with the findings of studies by Nyamwange et al, (2012), Mbongo, et al, (2016), Boit (2016) and Nkala (2014) that found lack of relevant resources and facilities a major factor impacting on the successful implementation of school guidance and counselling services. According to Wambu and Fisher (2015) there is no unified ethical code for school counsellors' in Kenya.…”
Section: Back Ground Of the Studysupporting
confidence: 92%
“…These problems are not, however, unique to Namibia, as there is also an increase in the divorce rate and in the number of single-parent families all over the world, which is also a stress factor for learners (Chireshe, 2011). Not only does the ever-increasing needs of children and the expectations of today's society impose growing demands on the education system, but also requires schools to find solutions and respond to these needs by providing counselling services to all learners to learn effectively (Mbongo, Möwes & Chata, 2016).…”
Section: Background and Contextmentioning
confidence: 99%
“…Although many studies have shed light on several counselling services offered in schools, (Mbongo, Möwes & Chata, 2016;Mushaandja, Haihambo, Vergnani & Frank, 2013;Talimethi & Mbewa, 2012;Alemu, 2013;Chireshe, 2011;Gallant & Zhao, 2011), there has been little evidence from a Namibian context. On this basis, the purpose of the study was to understand from the participants' perspective, the counselling services offered in Namibian schools and their effectiveness on enhancing students' self-knowledge and understanding.…”
Section: Background and Contextmentioning
confidence: 99%